2011
DOI: 10.1371/journal.pone.0022277
|View full text |Cite
|
Sign up to set email alerts
|

Strong Association of 677 C>T Substitution in the MTHFR Gene with Male Infertility - A Study on an Indian Population and a Meta-Analysis

Abstract: BackgroundMethylenetetrahydrofolate reductase (MTHFR) is an important enzyme of folate and methionine metabolism, making it crucial for DNA synthesis and methylation. The objective of this study was to analyze MTHFR gene 677C>T polymorphism in infertile male individuals from North India, followed by a meta-analysis on our data and published studies.Methodology/Principal FindingsWe undertook genotyping on a total of 837 individuals including well characterized infertile (N = 522) and confirmed fertile (N = 315)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 33 publications
4
59
0
Order By: Relevance
“…Many studies have revealed discrepant findings between Caucasians and Asians. 21,35,51 It seems most likely that this is related to dietary factors, such as folic acid intake; however; caution should be applied when generalizing the following recommendations to the Asian-American population.…”
Section: Acmg Practice Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have revealed discrepant findings between Caucasians and Asians. 21,35,51 It seems most likely that this is related to dietary factors, such as folic acid intake; however; caution should be applied when generalizing the following recommendations to the Asian-American population.…”
Section: Acmg Practice Guidelinesmentioning
confidence: 99%
“…20 The potential associations between MTHFR genotype status and a number of medical complications have been evaluated using methodologies such as case-control, cohort, Mendelian randomization, and meta-analysis. A modest positive association has been found between the MTHFR "thermolabile" polymorphism and many different medical complications, including, but not limited to, thromboembolic disease (in non-North-American populations only), 21,22 stroke, [23][24][25][26][27] aneurysm, 28 peripheral artery disease, 29 migraine, 30 hypertension, 31,32 recurrent pregnancy loss, 33,34 male infertility, 35,36 risk for offspring with neural tube defects, 37,38 certain cancers, [39][40][41] neuropsychiatric disease, 42 and chemotherapy toxicity. 43,44 …”
mentioning
confidence: 99%
“…A number of studies have evaluated the association of MTHFR gene polymorphism with male infertility [13, 38-40, 22, 27, 17, 16, 18, 29, 25, 41, 28, 42, 26, 21, 23]. The MTHFR C677T polymorphism was reported to be associated with male infertility in the German [42], Indian [26,18,17,38], Korean [23], Chinese [19] and Italian populations [41]. In contrast, Stuppia et al [28] and Ebisch et al [21] did not find any statistically significance of C677T variation in infertile men from Italy and the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of molecular epidemiological studies have been conducted to evaluate the role of the three folate-related enzyme gene (MTHFR, MTR and MTRR) polymorphisms in male infertility [11,13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. However, the association between polymorphism and the risk of male infertility is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some copy number variations (CNV) have been described to be associated with severe oligozoospermia or Sertoli-cell-only (SCO) syndrome or both [6]. In addition, some autosomal deletions, rare X-linked CNV, DNA repair mechanism defects, Y-linked syndromes, and some single nucleotide polymorphisms (SNPs) have been found to be associated with male factor infertility [7][8][9][10][11][12][13]. Although some specific mutations have been identified, other factors responsible for the sperm defects remain unknown.…”
Section: Introductionmentioning
confidence: 99%